청주지역 일부 대학생의 체중조절 식품 및 건강기능식품 사용 실태와 관련 인식 연구 - 김가영(Gayong Kim); 배문경(Munkyong Pae) (Korean journal of community nutrition, 2021)
Objectives: This study sought to assess the prevalence and duration of weight-control or health functional food use, associated weight-control behavior, perception, and knowledge among university students. Methods: The subjects were 442 university students in Cheonju, Korea, and data was collected by a self-administered questionnaire. Both χ2 and t-tests were conducted for categorical and mean comparisons. Results: An estimated 62.7% (female 69.0%, male 54.8%) had ever attempted weight-control. Among these, an estimated 59.2% of females and 38.9% of males had used weight-control or health functional foods with significant gender difference. The weight-control foods commonly used included chicken breast, protein powder, low-fat milk and soymilk, and meal replacement drinks, while garcinia cambogia extract and green tea extract were frequently used as health functional foods. One of 10 (10.3%) consumers of weight-control foods reported ≥ 7 months use, with less frequent long-term consumption of health functional foods (4.2%). The average degree of satisfaction was 3.24 ± 0.92 for weight-control foods and 2.72 ± 0.97 for health functional foods on a 5-point scale, meaning 'slightly satisfied' and 'slightly dissatisfied', respectively. Females or students with an experience of weight-control reported poorer perceptions of their health and body image as well as a higher need for weight control. Besides, both male and female subjects felt a high need for correct information regarding weight-control methods. Conclusions: Our results provide a better understanding of the characteristics associated with the use of weight-control or health functional foods among university students and will be useful in developing a nutrition education program by incorporating correct body image, knowledge, and practical yet desirable practices for weight control.